Heart failure in cardiomyopathies: a position paper from the Heart Failure Association of the European Society of Cardiology. (16th April 2019) - Seferović, Petar M.; Polovina, Marija; Bauersachs, Johann; Arad, Michael; Gal, Tuvia Ben; Lund, Lars H.; Felix, Stephan B.; Arbustini, Eloisa; Caforio, Alida L.P.; Farmakis, Dimitrios; Filippatos, Gerasimos S.; Gialafos, Elias; et al.
Abstract : Cardiomyopathies are a heterogeneous group of heart muscle diseases and an important cause of heart failure (HF). Current knowledge on incidence, pathophysiology and natural history of HF in cardiomyopathies is limited, and distinct features of their therapeutic responses have not been systematically addressed. Therefore, this position paper focuses on epidemiology, pathophysiology, natural history and latest developments in treatment of HF in patients with dilated (DCM), hypertrophic (HCM) and restrictive (RCM) cardiomyopathies. In DCM, HF with reduced ejection fraction (HFrEF) has high incidence and prevalence and represents the most frequent cause of death, despite improvements in treatment. In addition, advanced HF in DCM is one of the leading indications for heart transplantation. In HCM, HF with preserved ejection (HFpEF) affects most patients with obstructive, and ∼10% of patients with non‐obstructive HCM. A timely treatment is important, since development of advanced HF, although rare in HCM, portends a poor prognosis. In RCM, HFpEF is common, while HFrEF occurs later and more frequently in amyloidosis or iron overload/haemochromatosis. Irrespective of RCM aetiology, HF is a harbinger of a poor outcome. Recent advances in our understanding of the mechanisms underlying the development of HF in cardiomyopathies have significant implications for therapeutic decision‐making. In addition, new aetiology‐specific treatment options (e.g. enzyme replacement therapy, transthyretin stabilizers, immunoadsorption, immunotherapy, etc.) have shown a potential to improve outcomes. Still, causative therapies of many cardiomyopathies are lacking, highlighting the need for the development of effective strategies to prevent and treat HF in cardiomyopathies.